Manajemen Strategi Analisis SWOT pada UMKM: Studi Kasus: KOPIRATES – Maumere (Jurnal Manajemen Kreatif dan Inovasi, 2026)
Kopirates Maumere is a local micro, small, and medium enterprise (MSME) engaged in the processing and marketing of specialty coffee products from Sikka Regency. This study aims to analyze the management strategies implemented by the MSME based on interviews with the business owner. The research focuses on product strategy, marketing, operations, business development, and the challenges faced in running the MSME amid increasingly competitive market conditions. The research method employs a descriptive qualitative approach through in-depth interviews and direct observation. The results indicate that Kopirates Maumere applies a product differentiation strategy by highlighting the quality of local coffee, supported by increasingly developed digital marketing. The MSME also strives for operational efficiency despite facing challenges related to limited capital and production equipment. This study concludes that adaptive management strategies based on local potential are crucial for maintaining MSME sustainability. Furthermore, improved managerial capacity along with support from the government and local communities is needed to strengthen the MSME’s position in a broader market.